Portrayal Of The Protagonist Raziman In The Novel Gerila - Veeramuthu, Saravanan P.; Jamaludin, Akif Faizullah (International Journal of Psychosocial Rehabilitation, 2020)
This study looks at Raziman's character in a novel entitled Gerila. The main purpose of this article is to evaluate and explain the character traits of the main character. This study is textual and contextual study with particular focus on the novel written by the Patani community. The data for this study is from Lukman Iskandar's Gerila (2008) . The objectives of this study is to explore and discuss the issues concerning the line that distinguishes between nationalist and terrorist based on the selected theoretical frameworks to determine whether the main character in the selected novel was a terrorist or a nationalist. The Urban Terrorism framework by Richard Clutterbuck (1994) and a conceptual framework by Hans Kohn (1968) which underline the three main characteristics of nationalism will be used to discuss the traits of terrorists and nationalists respectively. The discussion will be based on the novel Gerila by Lukman Iskandar, to determine the role of the main character, Raziman. This discussion will attempt to determine whether Raziman in this novel fought in the Patani land as a terrorist or a nationalist based on the selected theoretical and conceptual frameworks. on the selected theoretical and conceptual frameworks.